2021
DOI: 10.1186/s43141-021-00200-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antimicrobial activities of some wild Egyptian mushrooms: Bjerkandera adusta as a promising source of bioactive antimicrobial phenolic compounds

Abstract: Background The discovery of potential, new cost-effective drug resources in the form of bioactive compounds from mushrooms is one way to control the resistant pathogens. In the present research, the fruiting bodies of five wild mushrooms were collected from Egypt and identified using internal transcribed spacer region (ITS) of the rRNA encoding gene and their phylogenetic relationships, antimicrobial activities, and biochemical and phenolic compounds were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…An HPLC-DAD-MS analysis was also carried out in order to measure the levels of selected phenolic and flavonoid compounds, namely, gallic acid, hydroxytyrosol, catechin, chlorogenic acid, epicatechin and benzoic acid, that play a major role in the antioxidant/antimicrobial response following mushroom extract administration [40,41]. Specifically, Table 1 shows that the level of gallic acid is higher in extracts A and C, whereas extract B do not show a relevant amount of this compound.…”
Section: Phenolic and Flavonoid Determination Via Hplc-dad-msmentioning
confidence: 99%
“…An HPLC-DAD-MS analysis was also carried out in order to measure the levels of selected phenolic and flavonoid compounds, namely, gallic acid, hydroxytyrosol, catechin, chlorogenic acid, epicatechin and benzoic acid, that play a major role in the antioxidant/antimicrobial response following mushroom extract administration [40,41]. Specifically, Table 1 shows that the level of gallic acid is higher in extracts A and C, whereas extract B do not show a relevant amount of this compound.…”
Section: Phenolic and Flavonoid Determination Via Hplc-dad-msmentioning
confidence: 99%
“…The lack of correlations in the content of these compounds with absorbance increases at 240 nm-250 nm [44] suggested that their biosynthesis was associated with the metabolism of B. adusta CCBAS 930. Earlier studies have shown that fungi, e.g., Bjerkandera adusta, synthesize phenolic compounds [45,46], and that the addition of exogenic phenolic acids increases the efficiency of the production of phenolic compounds [47]. Moreover, during the biotransformation of anthraquinone derivatives by B. adusta CCBAS 930, an increase in the content of phenolic compounds was observed [8].…”
Section: Discussionmentioning
confidence: 99%
“…20 Phylogenetic tree of xylanase proteins from A. terreus strain RGS. Eg-NRC was inferred using the neighbor-joining method (MEGA X) gene for fungal identification [12]. For example, a previous study [44] employed the ITS gene for the tion of some indigenous Beauveria isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to help with the production process of traditional meals and minimize toxins in various substrates, microorganisms (fungi), for example, Aspergillus terreus (A. terreus), have been implemented However, although some strains of A. terreus generate mycotoxins, which are toxic to both animals and humans [11], a preliminary assessment of mycotoxin production in Aspergillus was conducted. Their results showed nonexistent mycotoxin production [12]. Also, fermentation methods can improve food safety by lowering harmful chemicals during manufacturing [13].…”
Section: Introductionmentioning
confidence: 99%